Life of Fridtjof Nansen : scientist and explorer, including an account of the 1893-1896 expedition - Bain, J. Arthur (James Arthur)
Abridged edition entitled Fridtjof Nansen and expanded edition entitled Life and explorations of Fridtjof Nansen also published in 1897. Mode of access: Internet.